Something wild [videorecording (DVD)] - Daniels, Jeff, 1955-; Griffith, Melanie, 1957-; Liotta, Ray (Criterion collection, 2011)
A straitlaced businessman meets a quirky, free-spirited woman at a downtown New York greasy spoon. Her offer of a ride back to his office results in a lunchtime motel rendezvous, just the beginning of a capricious interstate road trip that brings the two face-to-face with their hidden selves.